2019
DOI: 10.1371/journal.pone.0215349
|View full text |Cite
|
Sign up to set email alerts
|

The poverty of adult morphology: Bioacoustics, genetics, and internal tadpole morphology reveal a new species of glassfrog (Anura: Centrolenidae: Ikakogi) from the Sierra Nevada de Santa Marta, Colombia

Abstract: Ikakogi is a behaviorally and morphologically intriguing genus of glassfrog. Using tadpole morphology, vocalizations, and DNA, a new species is described from the Sierra Nevada de Santa Marta (SNSM), an isolated mountain range in northern Colombia. The new taxon is the second known species of the genus Ikakogi and is morphologically identical to I . tayrona (except for some larval characters) but differs by its genetic distance (14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 73 publications
3
24
0
1
Order By: Relevance
“…A vent tube with dextral opening is found in Edalorhina , Engystomops , and most Physalaemus (Table S4). Among Leiuperinae, most Pleurodema and Pseudopaludicola have a medial vent tube (Andrade, Ferreira, Takazone, Libório, & Weber, 2018; Barrasso, Alcalde, Martinazzo, & Basso, 2012; Cei, 1980; Galvani, Gonzalez, Sanabria, & Quiroga, 2012; Kher & Schaefer, 2005; Kolenc et al, 2009; Laufer & Barreneche, 2008; Lobo, 1991; Magalhães, Loebmann, Kokubum, Haddad, & Garda, 2014; Pereira & Nascimento, 2004; Schulze et al, 2015; Toledo, 2010), a character‐state also found in most genera of Leptodactylidae (e.g., Almeida & Angulo, 2006; de Sá, Langone, & Segalla, 2007; Grosso, 2015; Heyer & Silverstone, 1969; Lamar & Wild, 1995; Magalhães, Garda, Amado, & de Sá, 2013; Menin, de Almeida, & Kokubum, 2009; Menin, Lima, & Rodrigues, 2010; Mêrces, Magalhaes, Amado, Junca, & Garda, 2015; Rossa‐Feres & Nonura, 2006; Schulze et al, 2015; Zaracho & Kokubum, 2017) as well as in many Centrolenidae, the sister group of Leptodactylidae (Jetz & Pyron, 2018; for centrolenids tadpoles, see Rada et al, 2019 and references therein). When we optimize this character on the phylogeny of Leiuperinae provided by Jetz and Pyron (2018), the presence of a dextral vent tube emerge as a synapomorphy of Edalorhina , Engystomops , and Physalaemus (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…A vent tube with dextral opening is found in Edalorhina , Engystomops , and most Physalaemus (Table S4). Among Leiuperinae, most Pleurodema and Pseudopaludicola have a medial vent tube (Andrade, Ferreira, Takazone, Libório, & Weber, 2018; Barrasso, Alcalde, Martinazzo, & Basso, 2012; Cei, 1980; Galvani, Gonzalez, Sanabria, & Quiroga, 2012; Kher & Schaefer, 2005; Kolenc et al, 2009; Laufer & Barreneche, 2008; Lobo, 1991; Magalhães, Loebmann, Kokubum, Haddad, & Garda, 2014; Pereira & Nascimento, 2004; Schulze et al, 2015; Toledo, 2010), a character‐state also found in most genera of Leptodactylidae (e.g., Almeida & Angulo, 2006; de Sá, Langone, & Segalla, 2007; Grosso, 2015; Heyer & Silverstone, 1969; Lamar & Wild, 1995; Magalhães, Garda, Amado, & de Sá, 2013; Menin, de Almeida, & Kokubum, 2009; Menin, Lima, & Rodrigues, 2010; Mêrces, Magalhaes, Amado, Junca, & Garda, 2015; Rossa‐Feres & Nonura, 2006; Schulze et al, 2015; Zaracho & Kokubum, 2017) as well as in many Centrolenidae, the sister group of Leptodactylidae (Jetz & Pyron, 2018; for centrolenids tadpoles, see Rada et al, 2019 and references therein). When we optimize this character on the phylogeny of Leiuperinae provided by Jetz and Pyron (2018), the presence of a dextral vent tube emerge as a synapomorphy of Edalorhina , Engystomops , and Physalaemus (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Larval morphology is an exciting field, and despite tadpoles having been studied for over 100 years (e.g., Boulenger, 1892; Lataste, 1879; Noble, 1929; Orton, 1953), as more species are investigated, new characters are described (e.g., Dias, Araújo‐Vieira, Santos, & Both, 2019b; Dias, Mongin‐Aquino, et al, 2018a; Haas et al, 2014; Rada et al, 2019; Rowley, Tran, Le, Hoang, & Altig, 2012; Vera Candioti et al, 2017). Even in phenotypically conserved lineages such as the genus Proceratophrys , new characters can be discovered as is the case of P. minuta .…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery of new species and new country records (e.g. Velásquez-Álvarez et al 2007;Rada et al 2017aRada et al , 2017bRada et al , 2019Thompson et al 2018; this work) exemplify this scenario. Thus, similar results are expected as fieldwork continues in poorly explored areas, such as the Andean/Amazonian and Andean/Chocoan forests.…”
Section: Discussionmentioning
confidence: 68%
“…Although Lynch et al (1997) estimated that only 10% of the centrolenid diversity in Colombia remained to be discovered, the number of species known to occur in the country has increased to 79 at present (Frost 2020). However, this number remains uncertain because taxonomic studies and fieldwork often result in names being resurrected or placed in synonym, the description of new taxa (Velásquez-Álvarez et al 2007;Guayasamin et al 2008;Rada et al 2017aRada et al , 2017bRada et al , 2019 and distribution extensions of species, including new country records (Malambo et al 2013(Malambo et al , 2017Molina-Zuluaga et al 2017;Thompson et al 2018).…”
Section: Introductionmentioning
confidence: 99%